Discursos e atitudes dos profissionais de saúde sobre o uso de álcool e outras drogas - Sabadini, Michaela Bitarello do Amaral [UNIFESP] (2010)
Introduction and aims: To explore the association between primary care professionals’ (PCPs) attitudes towards unhealthy alcohol and other drug (AOD) use (from risky use through dependence) and readiness to implement AOD-related preventive care. Design and Methods: PCPs from 5 health centers in Sao Paulo were invited to complete a questionnaire about preventive care and attitudes about people with unhealthy AOD use. Logistic regression models tested the association between professional satisfaction and readiness. Multiple Correspondence Analysis (MCA) assessed associations between stigmatizing attitudes and readiness. Results: Of 160 PCPs surveyed, 96 (60%) completed the questionnaire. Only 25% reported implementing unhealthy AOD use clinical prevention practices; and 53% did not feel ready to implement such practices. Greater satisfaction when working with people with AOD problems was significantly associated with readiness to implement AOD-related preventive care. In MCA two groups emerged: 1. PCPs ready to work with people with unhealthy AOD use, who attributed to such patients lower levels of dangerousness, blame for their condition and need for segregation from the community (suggesting less stigmatizing attitudes); 2. PCPs not ready to work with people with unhealthy AOD use, who attributed to them higher levels of dangerousness, blame, perceived level of patient control over their condition, and segregation (suggesting more stigmatizing attitudes). Discussion and conclusions: More stigmatizing attitudes towards people with unhealthy AOD use are associated with less readiness to implement unhealthy AOD-related preventive care. Understanding these issues is likely essential to facilitating implementation of preventive care, such as screening and brief intervention, for unhealthy AOD use.